A Fictional Case Study Involving Person-Centred Therapy and Transpersonal Psychotherapy in Conceptualizing and Treating Bulimia Nervosa - Kilrea, Kelly A.; Richer, Sheri (Canadian Journal of Counselling and Psychotherapy, 2017)
This fictional case study explores various components of person-centred therapy and transpersonal psychotherapy as applied to the conceptualization of a bulimia nervosa case study and psychotherapeutic treatment. The strengths and limitations of these theories in the conceptualization and treatment of bulimia nervosa are discussed.